Lipid profile: a conduit in the progression from psoriasis to cardiovascular disease - Sahu, Samir; Devi, Ellora; Poddar, Anirban; Ray, Subhashree (International Journal of Advances in Medicine, 2017)
Background: Psoriasis although a disease of the skin has been reported to be associated with metabolic syndrome. Metabolic syndrome in turn is associated with dyslipidemia which is a independent risk factor for cardiovascular diseases. Our study therefore aims to assess lipid profile in patients with psoriasis with an objective to observe and report any significant deviations in the same as compared to healthy controls. Methods: 25 patients with psoriasis and 25 age, sex matched healthy controls were recruited in this study and lipid profile was estimated using commercially available reagent kit which employs the CHOD-PAP method. Results: Significant elevation in levels of total cholesterol, triglycerides, VLDL and cholesterol/HDL ratio was observed. Elevated although was observed in case of LDL and HDL levels, but it was statistically insignificant. Conclusions: Dyslipidemia was found to be prevalent in psoriasis patients. Dyslipidemia is an independent risk factor for development of cardiovascular disease. Dyslipidemia in psoriasis therefore clearly suggests an inherent predisposition of psoriasis patients to suffer from cardiovascular diseases. A lipid profile estimation in these patients therefore might serve as an important tool for risk assessment for cardiovascular disease, thereby aiding a timely intervention.